Sensitivity Analysis of the Integrated CRITIC-TOPSIS Method for Selecting Optimal Natural Fibre–Reinforced Composites for Toe Caps in Safety Footwear - Ab Rahman, Mohd Hidayat; Jumaidin, Ridhwan; Mahmud, Jamaluddin; Abdul Rahman, Siti Mariam (Al-Khwarizmi Engineering Journal, 2026)
The selection of natural fibres for toe caps in safety footwear requires careful evaluation of multiple performance criteria. This process makes the task a multicriteria decision-making problem, as numerous alternatives and requirements must be considered simultaneously. This study applied the CRiteria Importance Through Intercriteria Correlation (CRITIC) method to compute objective criterion weights, which were then integrated into the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to rank and identify the optimum fibre amongst 12 alternatives. A sensitivity analysis was conducted to evaluate the impact of weight variations on the selection results. The combined CRITIC-TOPSIS method effectively determined the optimal natural fibre for safety toe cap applications. Sensitivity analysis confirmed the robustness of the results whilst highlighting the influence of criterion weight variations on final rankings. The proposed integration offers a systematic and reliable approach for material selection in safety footwear. The findings provide useful guidance for the development of natural fibre–reinforced polymer composites and support lightweight and sustainable alternatives for toe caps in safety footwear.